Policies of pedagogical maintenance of students ready for a safe life in inclusive education - Alexandrovna, Busygina Tatyana; Korostelev, Aleksandr A.; Artemova, Elena I.; Kolyvanova, Larisa Aleksandrovna; Nosova, Tamara Mikhailovna; Pavlov, Ivan Ivanovich; Thomas, Svetlana Mikhailovna (Cuestiones Políticas, 2020)
The article aimed to review some pedagogical policies for the inclusion and a safe life of people with disabilities. Training the preparation of people with disabilities and disabilities for a safe life is more effective within the framework of an accessible and organized educational environment in the educational institution, which guarantees the solution of professional problems in the training of future middle-level specialists. For a safe stay in society. Under the provision of people with health problems for a safe life, we consider the complex subjective property of a person with a disability, which manifests itself when it understands the dangers that have arisen in the educational environment and in various areas of life and we provide a way to overcome them. It is concluded that without an accessible and well-organized educational environment, it is impossible to achieve the result of establishing harmonious relationships between people with disabilities and the social environment that determine their greater disposition for a safe entry into society and a full life in modern society. Particular attention is paid in the process of vocational training for people with disabilities to individualization.